(untitled) - Higham, Charles (New York, 1989)
This important new synthesis focuses on the social world of early mainland Southeast Asia: Thailand, Vietnam, Kampuchea, Laos and adjacent areasSoutheast Asia was the scene of one of the world's major civilisations, that of Angkor, until it was sacked in the early fifteenth century.
Keywords: Antiquities, prehistoric,Cổ vật, thời tiền sử; Đông Nam Á; Southeast Asia